Perlindungan Hukum Konsumen dalam Transaksi Electronic Commerce melalui Bukalapak - Chandra Supriyanto; Hendra Djaja; Diah aju wisnuwardhani; Khotbatul Laila (Bhirawa Law Journal, 2020)
E-commerce transactions in this era become one of the business models that are in great demand by the people of Indonesia. The development and progress of information technology is so fast that it causes changes in the activities of human life in various fields which have directly affected the birth of new forms of legal action. Internet support makes online business more attractive to many people, because of the convenience offered. Marketplace or online trading sites become a new choice that offers convenience and security in e-commerce transactions. One marketplace that offers convenience and security in e-commerce transactions is Bukalapak. There is no comprehensive legal protection in accordance with the Rules for the Use of Bukalapak. Consumers are still the weakest party if a problem occurs because the model built contains a standard clause in it. Therefore, the protection of consumers in online buying and selling transactions needs to be considered